Der Regionale Flächennutzungsplan: Potenziale, Probleme und Lösungsansätze - Koch M.A., Robert (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
The “Regional Land Use Plan” (or „Regional Masterplan” — Gm. Regionaler Flächennutzungsplan) has been introduced to link regional and urban planning. Legislation (Section 9 VI of the German Federal Regional Planning Act — Raumordnungsgesetz-ROGJ requires this plan to be applied to entire regions and to comply with regional (ROG) and urban planning law (the Federal Building Code — Baugesetzbuch-BauGB). Due to its complexity, the Länder, regions and municipalities have not yet implemented regional masterplans. However, such plans could be simplified by suitable modifications, such as different levels of planning scales and concepts, as proposed by interviewed planners, since better results and efficiency and greater acceptance of this new plan type will depend significantly on closer co-operation among the municipalities in terms of planning concepts and strategies.